The Role Of Educators In Overcoming Student Development Problems At Uptd Smpn 6 Budong - Budong Central Mamuju District - Subur, Hikmayani; Wisudawaty, Ika (Cita konsultindo, 2024)
This research is to determine the role of educators in helping students to overcome student development problems at UPTD SMPN 6 Budong - Budong, Central Mamuju Regency. This research uses a literature study methodology, namely collecting information from various library sources, including scientific journals. The results of this research show that educators have an important role in helping students overcome problems; educators give examples, motivate, inspire and advise. Educators encourage all students to collaborate in order to increase mutual respect and respect in the classroom.